Humidity dependence of AE activity in sheared quartz gouges and its implication for the micromechanics of friction - Yasuo Yabe (Earth, Planets and Space)
Abstract The micromechanics of friction has been investigated from the viewpoint of the healing of real contacts. In this study, the underlying processes of friction are discussed from the viewpoint of the contact junction deformation and failure by measuring the acoustic emission (AE) activity associated with the frictional sliding. Sliding-rate step tests of synthetic quartz gouges sandwiched between metal forcing blocks are conducted using a low-speed (< 700 μm/s) rotary shear apparatus. Humidity is controlled to be dry (~ 5%RH), room (~ 40%RH), humid (100%RH), or wet (saturated without pore pressure control). The frictional behavior is modeled by the rate- and state-dependent friction (RSF) law with two state variables. Shorter critical slip distances of the state evolution would be about the contact junction size, while longer critical slip distances are close to the average diameter of gouge particles. The AE activities are evaluated by AE rate that is the number of AE events per unit sliding distance and the m-value that characterizes the amplitude distribution. As variations in AE activities and the evolution term ( $${b}_{1}$$ b 1 ) with the shorter critical slip distance highly correlate, AE activity may reflect the state of contact junction. While $${b}_{1}$$ b 1 increases with increasing water vapor from dry to humid, AE rate and the m-value are decreased. This may be caused by an increase in inelasticity of the contact junction deformation. Under wet conditions, $${b}_{1}$$ b 1 is similar to that under the humid condition, AE rate is further decreased but the m-value becomes significantly large. This is probably because the failure process of the contact junction changes to less brittle one, implying the impact of phase of water (vapor or liquid) on the brittleness of the failure processes of contact junction. Graphical Abstract